The Influence of Participative Leadership Style, Work Discipline, and Work Environment on Employee Performance at Cleanwear Indonesia Shoe Cleaning Store - Rhevuano Naoval Saputra; Acep Samsudin (International Journal of Social, Economic, and Business, 2025)
This study addresses the declining employee performance at CleanwearIndonesia, particularly evident in the significant increase in tardiness ratesobserved between April and September 2024. The research aims to analyzethe influence of participative leadership style, work discipline, and workenvironment on employee performance in the shoe cleaning service industry.Using a quantitative approach, data was collected through questionnaires witha Likert scale from employees at the Panglima Sudirman branch. The studyemployed multiple linear regression analysis using SPSS. Results indicate thatparticipative leadership style, work discipline, and work environmentsimultaneously have a significant effect on employee performance, with thesevariables explaining a portion of the variance in employee performance.Individual analysis reveals that participative leadership style and workenvironment have significant positive effects on employee performance,while work discipline shows no significant impact. The findings suggest thatorganizations in the service sector should focus on implementing participativeleadership approaches and maintaining an optimal work environment toenhance employee performance. This study contributes to the limited researchon human resource management in niche service industries, particularly in thecontext of digital transformation.